A-to-I RNA editing of CYP18A1 mediates transgenerational wing dimorphism in aphids - Bin Zhu; Rui Wei; Wenjuan Hua; Lu Li; Wenlin Zhang; Pei Liang (eLife)
Wing dimorphism is a common phenomenon that plays key roles in the environmental adaptation of aphid; however, the signal transduction in response to environmental cues and the regulation mechanism related to this event remain unknown. Adenosine (A) to inosine (I) RNA editing is a post-transcriptional modification that extends transcriptome variety without altering the genome, playing essential roles in numerous biological and physiological processes. Here, we present a chromosome-level genome assembly of the rose-grain aphid Metopolophium dirhodum by using PacBio long HiFi reads and Hi-C technology. The final genome assembly for M. dirhodum is 447.8 Mb, with 98.50% of the assembled sequences anchored to nine chromosomes. The contig and scaffold N50 values are 7.82 and 37.54 Mb, respectively. A total of 18,003 protein-coding genes were predicted, of which 92.05% were functionally annotated. In addition, 11,678 A-to-I RNA-editing sites were systematically identified based on this assembled M. dirhodum genome, and two synonymous A-to-I RNA-editing sites on CYP18A1 were closely associated with transgenerational wing dimorphism induced by crowding. One of these A-to-I RNA-editing sites may prevent the binding of miR-3036-5p to CYP18A1, thus elevating CYP18A1 expression, decreasing 20E titer, and finally regulating the wing dimorphism of offspring. Meanwhile, crowding can also inhibit miR-3036-5p expression and further increase CYP18A1 abundance, resulting in winged offspring. These findings support that A-to-I RNA editing is a dynamic mechanism in the regulation of transgenerational wing dimorphism in aphids and would advance our understanding of the roles of RNA editing in environmental adaptability and phenotypic plasticity.